Recovery trajectories and management responses for three scallop stocks over ten years following an extreme marine heatwave in Western Australia - Kangas, Mervi; Chandrapavan, Arani; Wilkin, Sharon; Caputi, Nick (Frontiers in Climate, 2022)
Saucer scallop, Ylistrum balloti, fisheries along central Western Australia was a key region impacted by the 2010/11extreme marine heatwave (MHW) when mean sea surface temperature anomalies reached up to 5oC between December and March. The extreme intensity and duration of this event had adverse impacts on survival of larval, juvenile, and adult scallops in the three major stocks in Shark Bay and at the Abrolhos Islands. The severe decline, observed from low commercial landings and verified through fishery-independent surveys required strong and rapid management response, and so in consultation with industry these commercial fisheries were closed to protect the remaining population and allow stock recovery. This provided an opportunity to examine other factors, in the absence of fishing, that may impact recovery. Fishing recommenced in Shark Bay after 3.5 years with one of the two stocks recovering more slowly whilst fishing recommenced in the Abrolhos Islands after 5 years. Differences in recovery rates between regions may be attributed to differences in life-history dynamics which vary with latitude. In Shark Bay, the austral summer is pre-spawning with peak spawning in the autumn/winter and therefore higher temperatures negatively impacted the spawning stock directly. In the Abrolhos Islands however, scallops had already spawned by summer and therefore the larvae and/or the early juveniles were impacted as well as post-spawned adults. Post 2011 MHW continued warmer ocean conditions were experienced, followed by four years (2016-2019) of a ‘marine cold spell’ then ‘short-lived’ moderate MHW during the summers of 2019/20 to 2021/22. Each stock has, over these years, responded differently to the conditions and fishing impacts and management responses also varied. We describe the science, management and industry response to severe stock declines, recovery rates, the drivers of recruitment and recovery and effects of recent summer MHWs on the current scallop stock status. Secondly, we describe the management arrangements and harvest strategies implemented. We highlight the importance of pre-season stock monitoring that provide a basis for catch/recruitment prediction and adaptive harvest strategies to ensure timely responses to stock declines in the event of extreme events expected to become more frequent in a changing global climate.